2013
DOI: 10.1111/codi.12380
|View full text |Cite
|
Sign up to set email alerts
|

A historical comparison of single incision and conventional multiport laparoscopic right hemicolectomy

Abstract: SILS offers a safe minimally invasive approach to right colon resection. In our series SILS patients had a shorter extraction wound size and shorter length of stay in hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Waters et al [20] reported a single death caused by substantial intra-operative bleeding. A single death also occurred in the study from Velthuis et al [27], caused by patient's significant comorbidities, while Keshava et al [32] also reported on a single perioperative death caused by neutropenic sepsis. Haas et al [31] also reported on a single death on the third postoperative day, caused by respiratory failure in the setting of pulmonary metastasis.…”
Section: Postoperative Outcomesmentioning
confidence: 83%
“…Waters et al [20] reported a single death caused by substantial intra-operative bleeding. A single death also occurred in the study from Velthuis et al [27], caused by patient's significant comorbidities, while Keshava et al [32] also reported on a single perioperative death caused by neutropenic sepsis. Haas et al [31] also reported on a single death on the third postoperative day, caused by respiratory failure in the setting of pulmonary metastasis.…”
Section: Postoperative Outcomesmentioning
confidence: 83%
“…Hand-assisted laparoscopic surgery does reduce the operating time, has reduced conversion rates and reduces the hazards of prolonged anaesthesia, hence should be in the armamentarium of surgeons [11] . Single port laparoscopic surgery (SPLS) is an attractive modification, although more data is required to prove its superiority over other techniques [12] . Limited data is available on the robotic -assisted dissection of rectum for IBD.…”
Section: Current Evidencesmentioning
confidence: 99%
“…Single-incision laparoscopic surgery is used for right-sided colon cancer. In a study comparing this technique with multiport laparoscopic resections for right hemicolectomy proved that the first technique is a safe approach in this type of colectomy, resulting in a smaller extraction orifice and shorter hospital stay [26]. The safety and efficacy of single-incision laparoscopic resection in stage IV colorectal cancer patients was assessed in a study and the results showed no significant differences in intra-and postoperative complications, 30day mortality rate, total lymph nodes, and postoperative hospital stay compared to the control group [27].…”
Section: Classification Of Laparoscopic Techniquesmentioning
confidence: 99%